Notes on the Microhabitats of the Philippine Discoglossid Frog Barbourula Busuangensis - Brown, Walter C.; Alcala, Angel C. (Silliman Journal, 2024)
The microhabitats of the Philippine discoglossid frog Barbourula busuangensis in permanent mountain streams in Northern Palawan are described. The water temperatures of these streams were about 25° C or lower. The juveniles were found in quiet, shallow pools, under rocks and among rotting leaves; the adults, under large boulders and inside crevices of rock-walls. The microhabitats of adults were all directly above water. Several species of anuran amphibian were associated with Barbourula.